2000
DOI: 10.1063/1.371833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of precursors and substrate materials on microstructure, dielectric properties, and step coverage of (Ba, Sr)TiO3 films grown by metalorganic chemical vapor deposition

Abstract: (Ba, Sr)TiO 3 (BST) thin films have been grown on planar Ir/Si and Pt/Si substrates and on three-dimensional (3D) Ir electrodes by metalorganic chemical vapor deposition using two kinds of β-diketonate-based BST precursors. Film growth was studied as a function of film thickness, composition, and substrate temperature. Growth rate was monitored by in situ spectroscopic ellipsometry. The BST films were characterized ex situ by a variety of techniques including x-ray photoelectron spectroscopy, Auger electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Previously it was reported that both thermal decomposition and oxidation of the precursor molecules occur in MOCVD growth using ␤-diketonate type sources. 18 However, at higher temperatures, thermal decomposition is dominant. From our results, it appears that above ϳ798 K the rate of thermal decomposition of the Co precursor molecules is notably greater than that of the Zn precursor molecule.…”
Section: A Film Compositionmentioning
confidence: 99%
“…Previously it was reported that both thermal decomposition and oxidation of the precursor molecules occur in MOCVD growth using ␤-diketonate type sources. 18 However, at higher temperatures, thermal decomposition is dominant. From our results, it appears that above ϳ798 K the rate of thermal decomposition of the Co precursor molecules is notably greater than that of the Zn precursor molecule.…”
Section: A Film Compositionmentioning
confidence: 99%
“…Fig. 15 compares the potential distribution of the proposed device with different RFP step-coverages, where the step-coverage is defined as the ratio of the sidewall thickness to the bottom thickness [40]. With the increase in step-coverage, RFP at the bottom sustains more voltage than that on the sidewall, and the potential distribution becomes not uniform which impacts BV and changes the breakdown point.…”
Section: Discussion On Fabricationmentioning
confidence: 99%
“…BST film can be produced using fairly simple equipment on a tight budget and in relatively short time [9][10][11]. In the film-producing process, there are a number of methods that could be used such as the metalorganic chemical vapor deposition (MOCVD) method [12][13][14], the chemical vapor deposition method [15], the sol-gel method [16][17][18][19], the atomic layer deposition (ALD) method [20], the pulsed laser ablation deposition (PLAD) method [21,22], rf sputtering [17,23,24], and chemical solution deposition (CSD) method [24][25][26][27][28][29][30][31]. The CSD method is superior as it can control the film stoichiometry with good quality, an easy procedure, and has a fairly affordable cost [32][33][34].…”
Section: Introductionmentioning
confidence: 99%